2011
DOI: 10.4038/sjae.v4i0.3482
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Tenancy Status on Productivity and Efficiency: Evidence from Fiji

Abstract: Productivity differences between tenant and owner operated farms have often been investigated using traditional methods. All these studies compute the partial productivity differences between the two farm ownership types. This paper takes the analysis one step further by examining the differences in efficiency among these two farm types. A stochastic frontier production function analysis reveals significant differences between the two farms with respect to input usage, productivity and technical efficiency. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Land fertility is expected to impact positively on TE, while land slope is expected to impact negatively on TE. Moreover, following Reddy (2002), we include total cultivated land area as an additional explanatory variable to examine whether small farmers are more efficient than large farmers.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…Land fertility is expected to impact positively on TE, while land slope is expected to impact negatively on TE. Moreover, following Reddy (2002), we include total cultivated land area as an additional explanatory variable to examine whether small farmers are more efficient than large farmers.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…Lack of such analysis will have weak and inadequate policy implications, which may fall short of achieving the desired goal. Literature on land tenure has revealed that, as income increases, the incidence of land disputes and land grabbing, and tenure insecurity increases (Reddy, 2002). Insecurity in ownership of land has negative impacts on productivity.…”
Section: Introductionmentioning
confidence: 99%